Ring-like Bright Monster Waves in Variable-Coefficient Partially Nonlocal Coupled NLS Equations with Directional Diffraction and External Perturbations in (3+1)D - Emmanuel Yomba (Mathematics)
Partially nonlocal (PNL) variable-coefficient nonlinear Schrödinger equations (NLSEs) represent a significant area of study in mathematical physics and quantum mechanics, particularly in scenarios where potential and coefficients vary spatially or temporally. The (3+1)-dimensional partially nonlocal (PNL) coupled nonlinear Schrödinger (NLS) model, enriched with different values of two transverse diffraction profiles and subjected to gain or loss phenomena, undergoes dimensional reduction to a (2+1)-dimensional counterpart model, facilitated by a conversion relation. This reduction unveils intriguing insights into the excited mechanisms underlying partially nonlocal waves, culminating in analytical solutions that describe high-dimensional extreme waves characterized by Hermite–Gaussian envelopes. This paper explores novel extreme wave solutions in (3+1)-dimensional PNL systems, employing Hirota’s bilinearization method to derive analytical solutions for ring-like bright–bright vector two-component one-soliton solutions. This study examines the dynamic evolution of these solutions under varying dispersion and nonlinearity conditions and investigates the impact of gain and loss on their behavior. Furthermore, the shape of the obtained solitons is determined by the parameters s and q, while the Hermite parameters p and n modulate the formation of additional layers along the z-axis, represented by <semantics>p+1</semantics> and <semantics>n+1</semantics>, respectively. Our findings address existing gaps in understanding extreme waves in partially nonlocal media and offer insights into managing these phenomena in practical systems, such as optical fibers. The results contribute to the theoretical framework of high-dimensional wave phenomena and provide a foundation for future research in wave dynamics and energy management in complex media.